PENYULUHAN PENGGUNAAN ANTIBIOTIK KEPADA MASYARAKAT DESA MANTUIL (PULAU BROMO) KOTA BANJARMASIN - Iqlima Iqlima; Muliyani Muliyani; Nazhipah Isnani; Muhammad Zaini (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2021)
Antibiotics are drugs used to kill bacteria so they are used to treat infections. Treatment with antibiotics must be on a doctor's prescription. The misuse of antibiotics can pose a dangerous risk of resistance. WHO has stated that deaths caused by antibiotic resistance reached 700,000 people in 2013. Education on the proper use of antibiotics aims to increase public awareness and understanding of how to use antibiotics correctly and appropriately. The implementation of this service in the form of counseling was carried out in Mantuil Village (Bromo Island) Banjarmasin City. The method used is through oral presentations delivered by pharmacists, questions and answers, and mini-quizzes. The results of this educational activity on the use of antibiotics have a positive influence on the entire community as evidenced by the community answering correctly on every given mini-quizes. The community is also active in asking questions about the use of antibiotics so that the community is considered enthusiastic in participating in the educational activity. It can be concluded that with this activity, the community becomes more aware of the proper and correct use of antibiotics.